Association of Heart Failure With Outcomes Among Patients With Peripheral Artery Disease: Insights From EUCLID - Samsky Marc D; Hellkamp Anne; Hiatt William R; Fowkes F Gerry R; Baumgartner Iris; Berger Jeffrey S; Katona Brian G; Mahaffey Kenneth W; Norgren Lars; Blomster Juuso I; Rockhold Frank W; DeVore Adam D; et al. (WILEY, 2022)
Background Peripheral artery disease (PAD) and heart failure (HF) are each independently associated with poor outcomes. Risk factors associated with new-onset HF in patients with primary PAD are unknown. Furthermore, how the presence of HF is associated with outcomes in patients with PAD is unknown.
Methods and Results This analysis examined risk relationships of HF on outcomes in patients with symptomatic PAD randomized to ticagrelor or clopidogrel as part of the EUCLID (Examining Use of Ticagrelor in Peripheral Arterial Disease) trial. Patients were stratified based on presence of HF at enrollment. Cox models were used to determine the association of HF with outcomes. A separate Cox model was used to identify risk factors associated with development of HF during follow-up. Patients with PAD and HF had over twice the rate of concomitant coronary artery disease as those without HF. Patients with PAD and HF had significantly increased risk of major adverse cardiovascular events (hazard ratio [HR], 1.31; 95% CI, 1.13-1.51) and all-cause mortality (HR, 1.39; 95% CI, 1.19-1.63). In patients with PAD, the presence of HF was associated with significantly less bleeding (HR, 0.65; 95% CI, 0.45-0.96). Characteristics associated with HF development included age >= 66 (HR, 1.29; 95% CI, 1.18-1.40 per 5 years), diabetes mellitus (HR, 1.85; 95% CI, 1.41-2.43), and weight (bidirectionally associated, >= 76 kg, HR, 0.77; 95% CI, 0.64-0.93; <76 kg, HR, 1.12; 95% CI, 1.07-1.16).
Conclusions Patients with PAD and HF have a high rate of coronary artery disease with a high risk for major adverse cardiovascular events and death. These data support the possible need for aggressive treatment of (recurrent) atherosclerotic disease in PAD, especially patients with HF.